2016
DOI: 10.1016/j.jnucmat.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of high energy cascade in ordered alloys: Defect production and subcascade division

Abstract: Displacement cascades have been calculated in two ordered alloys (Ni 3 Al and UO 2 ) in the molecular dynamics framework using the CMDC (Cell Molecular Dynamics for Cascade) code (J.-P. Crocombette and T. Jourdan, Nucl. Instrum. Meth. B 352, 9 (2015)) for energies ranking between 0.1 and 580keV. The defect production has been compared to the prediction of the NRT (Norgett, Robinson and Torrens) standard. One observes a decrease with energy of the number of defects compared to the NRT prediction at intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The above efficiency function tends to 0 by increasing the damage energy. However, the defect production is a linear function of the damage energy after the formation of displacement sub-cascade at high energy collisions [8,9]. The efficiency should thus be a constant after the subthreshold energy, which defines the threshold of subcascade formation.…”
Section: Methodsmentioning
confidence: 99%
“…The above efficiency function tends to 0 by increasing the damage energy. However, the defect production is a linear function of the damage energy after the formation of displacement sub-cascade at high energy collisions [8,9]. The efficiency should thus be a constant after the subthreshold energy, which defines the threshold of subcascade formation.…”
Section: Methodsmentioning
confidence: 99%
“…The former corresponds to displaced atoms calculated in SRIM, whereas the latter is related to the actual number of defects introduced in the MD cells, which fully contribute to the evolution of defects. It is known that the SRIM results tend to overestimate the actual defect numbers, i.e., the remaining displacements after potential recombination [60,61].…”
Section: Disordering Kineticsmentioning
confidence: 99%
“…As shown in ref. [61], the discrepancy between BCA models and MD calculations intensies with increasing the primary knock-on atoms (PKA) energy, with much less surviving defects in MD (than for BCA) at high energy. In the current case, the median PKA energy of 500 keV Ce ions is obviously larger than that of 20 keV He ions.…”
Section: Elastic Strain Kineticsmentioning
confidence: 99%
“…W [31], where a re-increase of the damage production seems to take place at high PKA energies. In the same way, it has been shown that the arc-dpa formula is not applicable to alloys or multi-elemental solids [32]. Its utility and field of application appears therefore quite restricted.…”
Section: Choice Between Qc and Fcmentioning
confidence: 99%